2021
DOI: 10.2147/copd.s307164
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Length of Hospital Stay Among Patients with Chronic Obstructive Pulmonary Disease (COPD) in Macao Population: A Retrospective Study of Inpatient Health Record

Abstract: This study aims to identify the effects of patient and clinical therapy factors on the length of hospital stay (LOS) for admission due to chronic obstructive pulmonary disease (COPD) in Macao. Patients and Methods: Health record of patients with COPD admitted to Kiang Wu Hospital from January 2017 to December 2019 was retrospectively analyzed. Demographic information, blood test results, clinical therapies, and LOS were described and analyzed by multivariable regression. Results: A total of 1116 admissions wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 57 publications
2
15
0
Order By: Relevance
“…Our study showed a significant association between length of stay with the number of comorbidities COPD patients were having at admission. Four out of five COPD inpatients in this study had at least one comorbidity, which was similar to previous studies [ 8 , 14 , 15 ]. A similar association has been established by various studies, thus reaffirming comorbidities as an important predictor of prolonged hospitalization [ 10 , [16] , [17] , [18] , [19] ].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our study showed a significant association between length of stay with the number of comorbidities COPD patients were having at admission. Four out of five COPD inpatients in this study had at least one comorbidity, which was similar to previous studies [ 8 , 14 , 15 ]. A similar association has been established by various studies, thus reaffirming comorbidities as an important predictor of prolonged hospitalization [ 10 , [16] , [17] , [18] , [19] ].…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the length of stay was significantly associated with the use of mechanical ventilatory support for the COPD patients during the inpatient stay. Similarly, an association between inpatient stay and mechanical ventilation has been seen in studies from India and Macau [ 8 , 27 ]. The study of Lindenauer et al showed that COPD patients treated with noninvasive ventilation at the time of hospitalization had lower inpatient mortality, shorter length of stay, and lower costs compared with those treated with IMV [ 28 ].…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Older COPD patients generally have a higher risk of acute exacerbations, leading to increased LOS. The prevalence of COPD in older patients has a negative impact on the length of stay (Li et al, 2021). The results of research conducted by Agboado et al (2012) found a significant increase in the LOS of patients aged 80 years and over compared to patients aged 40-59 years.…”
Section: Resultsmentioning
confidence: 99%